Analisis Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien Rawat Jalan di Puskesmas Mojosongo Boyolali yang Dimoderasi oleh Jenis Pembayaran - Elsa Melva; Aries Widiyoko; Sri Wulandari (MEDIKA TRADA, 2026)
Service quality is a factor that can influence the level of patient satisfaction in obtaining health services. This study aims to determine how service quality can influence outpatient satisfaction with the type of payment as a moderating variable at the Mojosongo Boyolali Community Health Center. This study used a quantitative analytical method with a cross-sectional approach. The number of samples in this study was 355 respondents selected using a simple random sampling technique. Data were collected by distributing questionnaires with a Likert scale of 1 to 4 to patients at the Mojosongo Boyolali Community Health Center. Data analysis used validity tests, reliability tests, and Moderated Regression Analysis (MRA) tests. The results showed that service quality can influence outpatient satisfaction with a significance value of 0.000 (<0.05) and a coefficient of determination (R2) of 0.682. The results of the moderation test showed that the type of payment was unable to moderate the effect of service quality on patient satisfaction with a significance value of the interaction variable of 0.054 (>0.05). This indicates that the type of payment does not influence the extent of patient satisfaction. Therefore, to increase the satisfaction of outpatients at the Mojosongo Boyolali Community Health Center, comprehensive improvements in service quality need to be continuously carried out.